International perspectives in social justice programs at the institutional and community levels - Sengupta, Enakshi; Blessinger, Patrick (Innovations in higher education teaching and learning ;, 2021)
Universities and faculty members play a vital role in providing education that helps build a strong foundation for a society where people are respected, treated equally, and get equal opportunities for upward social mobility. This book addresses the role of education in uplifting people out of poverty and oppression by imparting social justice education at the institution and community level. Including chapters dedicated to human rights education, the authors consider how educators can help to foster a sense of awareness among learners about the dignity of human life through various interventional programmes. Discussing human rights with respect to migrant workers, foster youth and prisoners in different countries, the chapters demonstrate how students from all levels can benefit from social justice education.